Squalene Biosynthesis in Engineered Escherichia Coli - Zhang, Wei; Li, Yuan; Xie, Li-Ping; Hu, You-Jia (Pharmaceutical Fronts, 2023)
Squalene is a natural triterpenoid that is important in medicine, and daily-use chemical and nutraceutical industries. The demand for squalene remains high and constant. Shark liver oil is the source of the compound; however, the source is unsustainable due to the protection of the gradually extinct animal. This study aimed to construct an engineered Escherichia coli strain to produce squalene in a green and sustainable manner. In this study, the activity of several squalene synthases from different species was screened. Gas chromatography-mass spectrometry and high-performance liquid chromatography were used for chemical structure identification. The mevalonate pathway (MVA) was constructed into BL21(DE3) to enhance the supply of farnesyl diphosphate to obtain squalene at a concentration of 69.3 mg/L. IspH was overexpressed in BL21(DE3) to decrease squalene production due to the accumulation of dimethylallyl diphosphate. By balancing the overexpression of ispH and ispG, the production of squalene increased to 298.3 mg/L. The genes of the MVA pathway were further separated upstream and downstream, and constructed into two plasmids with different origins to balance the metabolic flux. By optimizing the expression strength of genes in MVA and 2-C-methyl-d-erythritol-4-phosphate pathway, an engineered strain was finally obtained with squalene production of 974.3 mg/L. By replacing chassis cell BL21(DE3) with XL1-Blue, squalene production was further increased to 1,274 mg/L.
Keywords: squalene; MVA; MEP; biosynthesis; Escherichia coli